Research on Ground Contact Characteristics and Influencing Factors of Tires with Complex Tread Patterns Based on Inverse Modeling - Xianbin Du; Haoyu Li; Mengdi Xu; Yunfei Ge (Lubricants)
The contact characteristics of radial tires are crucial for optimizing stress distribution, deformation, and wear. The non-uniform contact stress behavior induced by complex tread patterns remains under-explored in existing tire mechanics research. Taking the 205/50R17 radial tire as a representative case, a reverse modeling approach was employed to develop an accurate finite element model for tires incorporating intricate tread pattern features. The fidelity of the proposed tire simulation model was confirmed utilizing high-precision contour profiling techniques. The impact of diverse usage conditions and design parameters on the tire outer profile and ground contact characteristics under static and free-rolling states was analyzed. Experimental observations demonstrate that the increased inflation pressure leads to a proportional decrease in contact area. Under incremental vertical loading, the contact patch develops progressively into a saddle-shaped geometry featuring elevated shoulder regions and a recessed central zone. Increasing the belt angle compromises its hoop-stiffening function, thereby inducing elliptical contact patch geometry. Larger design diameters compromise contact length symmetry in shoulder regions. Variation in shoulder thickness at 85% of the tread width results in a significant difference in contact length between the left and right tread blocks in the rolling state. This work enables refinement strategies for both tread configurations and tire dimensional designs in industrial applications.